THE FACTORS INFLUENCING DECREASE IN STUNTING PREVALENCE AMONG TODDLERS IN THE WORKING AREA GLUGUR DARAT COMMUNITY HEALTH CENTER, EAST MEDAN DISTRICT, MEDAN CITY - Turnip, Rita; Efendy, Ismail; Nasution, Ramadhani Syafitri (HEARTY, 2024)
The World Health Organization (WHO) estimates that 165 million children under the age of 5 in the world will be affected by malnutrition if efforts to reduce the prevalence of stunting continue on an ongoing basis, this is projected to be 127 million in 2025. Data from the Glugur Darat Health Center, the incidence of stunting in 2023 was 5 people cases, while 24 people experienced malnutrition. The aim of the research is to determine the factors that influence the reduction in the incidence of stunting among toddlers in the Glugur Darat Health Center Working Area, East Medan District, Medan City. The research design uses quantitative with a cross sectional approach. The population in this study were all mothers who had toddlers at the Glugur Darat Community Health Center, East Medan District, Medan City, namely 6,672 toddlers, with a sample size of 99 mothers who had toddlers. Data analysis uses univariate, bivariate and multivariate analysis. The results of the research show that there is an influence of food provision, personal hygiene, parenting patterns, utilization of health services on reducing the incidence of stunting among toddlers in the Glugur Darat Health Center Working Area, East Medan District, Medan City. Meanwhile, the most dominant factor is food provision. The conclusion of this research is that there is an influence of food provision, personal hygiene, parenting patterns, utilization of health services on reducing the incidence of stunting in toddlers in the Glugur Darat Health Center Working Area, East Medan District, Medan City. It is recommended that the Glugur Darat Health Center be able to create interesting education for mothers with toddlers so that they want to monitor their children at the puskesmas or posyandu, such as conducting workshops/demonstrations on how to provide good and correct and nutritious food for their children, as well as how to process it. diverse and nutritious food so that children get good nutritional intake as an early effort to reduce the incidence of stunting and improve family health.